Hubungan pengetahuan dan sikap terhadap kepatuhan diet diabetes mellitus pada pasien rawat jalan di RSU Kota Langsa - Keumalahayati Keumalahayati; Supriyanti Supriyanti; Kasad Kasad (Politeknik Kesehatan Kemenkes Aceh, 2019)
Background: Diabetes mellitus is a disease with abnormalities in glucose metabolism (a type of sugar monosaccharide in the body) of the human body. As a non-communicable disease, which lasts long or chronic and is characterized by high blood sugar levels. Healing in patients with diabetes mellitus is very closely related to adherence. Good compliance with patients depends on their knowledge and attitude in maintaining health status.Objectives: To measure the level of relationship between knowledge and attitudes of patients with diabetes mellitus to adherence to the diabetes mellitus diet in the outpatient ward of Langsa city hospital.Methods: Analytical research has been carried out using a cross-sectional design. Samples have been taken totaling 43 people, sampling by accidental sampling. Data collection was carried out by interview and observation using a structured questionnaire. Data processing was computerized and analyzed using the chi-square test at CI: 95%.Results: Showed that there was proportionate relationship between knowledge and diabetes mellitus diet adherence (p= 0.041), and the patient's attitude also show a relationship with diet adherence by diabetes mellitus patients in Langsa City Hospital (p= 0.021).Conclusion: The level of knowledge and attitude of patients in responding to the degree of health is not related to diet adherence carried out by patients with diabetes mellitus in Langsa City Hospital. Suggestions, it is necessary to increase by health workers in providing information on the adherence to the diabetes mellitus diet that is being carried out by people with diabetes mellitus in outpatients, to be implemented at home obediently and correctly.